Priority areas of police bodies’ activity in ensuring the citizens’ rights in the conditions of martial law legal regime in Ukraine - O. I. Bezpalova (Law and Safety)
The specifics of the activities of the police bodies regarding the protection of citizens' rights during the legal regime of martial law have been disclosed. The differences in the powers granted to police bodies in peacetime and during countermeasures against internal threats of martial law have been characterized. Factors, due to which the police authorities significantly reduced the number of administrative and criminal offenses, the commission of which prevailed in peacetime have been established.